PSEUDOPOTENTIAL MODEL AND CORRELATION FUNCTIONS OF SEMICLASSICAL PARTIALLY IONIZED PLASMAS - Davletov, A.E. (Recent Contributions to Physics, 2008)
Pseudopotential model of particle interaction in semiclassical partially ionized plasmas, taking into account both quantum-mechanical effects and presence of the neutral component (atoms), is proposed. Radial distribution functions and static structure factors are investigated for he case of hydrogen plasmas. Possibility of the short-range order formation is shown for the plasma-neutral gas system even for small values of the coupling parameter related to the nonideality in particle interaction.